Transformation of Learning Al-Qur'an Hadith with Big Book Media at Madrasah Ibtidaiyah Thoriqun Najah - Endang, Ujang; Daryaman (CV Kalimasada Group, 2024)
In the context of learning activities at Madrasah Ibtidaiyah Thoriqun Najah, several problems have been faced, such as low student learning outcomes, shortcomings in teacher administration, and limited learning media. This research aims to explore how to improve the quality of learning in the era of globalization. The method used is Classroom Action Research (PTK) with data collection techniques through observation, tests, and qualitative data analysis. The results showed an improvement in the preparation of the Learning Implementation Plan (RPP), teacher performance, and student learning outcomes with the use of